Meningoencephalitis due to anthrax: CT and MR findings - Yildirim, Hanefi; Kabakus, Nimet; Koc, Mustafa; Murat, Ayse; Girgin, Feyza Incekoey (Springer, 2006)
Anthrax is primarily a disease of herbivores, but it also causes cutaneous, respiratory and gastrointestinal infections in humans. Bacillus anthracis is an uncommon cause of meningitis and generally produces a haemorrhagic meningoencephalitis. We present the CT and MR findings of anthrax meningoencephalitis due to the cutaneous form of anthrax in a 12-year-old boy. They showed focal intracerebral haemorrhage with leptomeningeal enhancement.
Keywords: anthrax; encephalitis; CT; MRI